Desenvolvimento e caracterização de um compósito matriz metálica (CMM): aço EUROFER97 reforçado com Carbeto de Tântalo - TaC - Oliveira, Leiliane Alves de (2013)
Steel is an alloy EUROFER promising for use in nuclear reactors, or in applications where the material is subjected to temperatures up to 550 ° C due to their lower creep resistance under. One way to increase this property, so that the steel work at higher temperatures it is necessary to prevent sliding of its grain boundaries. Factors that influence this slip contours are the morphology of the grains, the angle and speed of the grain boundaries. This speed can be decreased in the presence of a dispersed phase in the material, provided it is fine and homogeneously distributed. In this context, this paper presents the development of a new material metal matrix composite (MMC) which has as starting materials as stainless steel EUROFER 97, and two different kinds of tantalum carbide - TaC, one with average crystallite sizes 13.78 nm synthesized in UFRN and another with 40.66 nm supplied by Aldrich. In order to improve the mechanical properties of metal matrix was added by powder metallurgy, nano-sized particles of the two types of TaC. This paper discusses the effect of dispersion of carbides in the microstructure of sintered parts. Pure steel powders with the addition of 3% TaC UFRN and 3% TaC commercial respectively, were ground in grinding times following: a) 5 hours in the planetary mill for all post b) 8 hours of grinding in the mill Planetary only for steel TaC powders of commercial and c) 24 hours in the conventional ball mill mixing the pure steel milled for 5 hours in the planetary mill with 3% TaC commercial. Each of the resulting particulate samples were cold compacted under a uniaxial pressure of 600MPa, on a cylindrical matrix of 5 mm diameter. Subsequently, the compressed were sintered in a vacuum furnace at temperatures of 1150 to 1250 ° C with an increment of 20 ° C and 10 ° C per minute and maintained at these isotherms for 30, 60 and 120 minutes and cooled to room temperature. The distribution, size and dispersion of steel and composite particles were determined by x-ray diffraction, scanning electron microscopy followed by chemical analysis (EDS). The structures of the sintered bodies were observed by optical microscopy and scanning electron accompanied by EDS beyond the x-ray diffraction. Initial studies sintering the obtained steel EUROFER 97 a positive reply in relation to improvement of the mechanical properties independent of the processing, because it is obtained with sintered microhardness values close to and even greater than 100% of the value obtained for the HV 333.2 pure steel as received in the form of a bar